Historical Pathways of National Research and Development Systems in OECD Countries - Gutiérrez Rojas, Cristián (2024)
Research and development (R&D) is crucial for promoting knowledge generation as well as the acquisition of new knowledge, so as to enable the development of new products, processes, or services, and improve the existing ones. In this vein, countries make decisions to increase and sustain their innovation efforts and focus on public R&D expenditures. This paper seeks to analyse the pathways of national R&D systems of OECD countries. For this purpose, we conducted a descriptive and exploratory analysis for the period of 2000-2021. We used innovative effort variables, such as R&D intensity, as well as patents as an output variable. The sample consisted of 37 OECD countries, divided into five quintiles according to productivity performance during the study period. The results highlight cases of R&D systems that made a significant leap in productivity during the study period; however, the results also identify cases where a higher R&D intensity does not translate into substantial improvements in productivity. This confirms that innovation is a complex phenomenon where there is not always a guarantee of a positive linear relationship between innovative effort and scientific/technological performance.